Approach to establishing and evaluating clinical relevance of drugs interactions in HIV patients : 2009 update (2010)
ABSTRACT: Objective: To update information on drug interactions in patients with HIV/AIDS. Method: PubMed was used to review English and Spanish articles published between 1 July 2007 and 30 April 2009 on antiretroviral drug interactions in humans. The search included a review of interactions between commonly-used medications in patients with HIV/AIDS and references from articles considered to be relevant. Results: Fifty two new interactions were identified having to do with CYP3A4 metabolism and competition for intestinal absorption. New pharmacokinetic interactions were identified for medications that were already on the market, and we report interactions for drugs that were recently introduced: Tipranavir, Fosamprenavir, Darunavir, Raltegravir, Maraviroc and Etravirine. Conclusions: There is evidence of 52 new interactions between medications using metabolic routes in the CYP450 enzymatic system, and an explanation is given for others in the intestinal absorption process.